Challenging Aspects of Teaching Writing through Online Learn-ing at Senior High School - Anugrah, Syahvira Zakiyyah Azmi; Devanti, Yeni Mardiyana; Astutik, Indri (Universitas Muhammadiyah Jember, 2023)
Writing is one of the most important skills that English students need to master. Writing is a difficult skill to master due to the lack of vocabulary, grammar, and ideas. The research design is a mixed method (Qualitative quantitative research). Data collected in two ways: Conduct a questionnaire in the form of Google forms application and interview with the teachers through Goggle Meetings. This research is dealing with four respondents from two different schools. This research proposes the question, “What are the challenging aspects faced by English teachers in teaching writing descriptive text and how do they encounter them?”. Based on the data, in the face of poor communication and lack of motivation, they provide platforms and applications for teachers to monitor and ensure good communication with students using Google Classroom and WhatsApp. Teachers also encourage students to follow up by providing the teachers’ number so that they can chat privately with the teacher if they do not understand the material or the assignment. Due to a lack of financial resources and lack of access mainly to internet data, the teachers gave the students some time to complete their assignments and suggested they use the school’s Wi-Fi.